Analysis of Business Actors' Understanding of Halal Certification Regulations in Kediri - Ning Purnama Sariati; Binti Mutafarida (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
The global halal lifestyle trend has driven significant growth in halal certification among micro, small, and medium enterprises (MSMEs) in Indonesia, including through the free SEHATI program, as the global halal market reaches USD 2 trillion annually. However, a critical gap remains between the sharp rise in certificate ownership and business actors' substantive understanding of halal regulations. This study aims to analyze the extent to which halal-certified MSMEs in Kediri City understand halal certification regulations, including concepts of halal and haram, the Quranic basis and MUI fatwas, critical points of haram, identification of impure materials, and the role of LPPOM MUI. A qualitative descriptive approach was employed, using in-depth interviews, observation, and documentation. Informants were selected through snowball sampling, and data validity was ensured through source triangulation. The findings reveal an 82% increase in the number of halal certification assistants at IAIN Kediri, while the number of halal certificates issued reached 99%. Nevertheless, all informants possessed only a partial, symbolic understanding, primarily focused on halal labels rather than on systematic halal assurance. Most did not understand the critical points, post-certification obligations, or the function of LPPOM MUI. This study concludes that achieving an administrative certificate does not guarantee regulatory compliance; therefore, ongoing mentorship and post-certification supervision are urgently recommended. Tren gaya hidup halal global telah mendorong peningkatan signifikan sertifikasi halal pada usaha mikro, kecil, dan menengah (UMKM) di Indonesia, termasuk melalui program SEHATI gratis, dengan pasar halal dunia mencapai USD 2 triliun per tahun. Namun, terdapat kesenjangan kritis antara peningkatan kepemilikan sertifikat halal dan pemahaman substansial pelaku usaha terhadap regulasi halal. Penelitian ini bertujuan menganalisis sejauh mana UMKM tersertifikasi halal di Kota Kediri memahami regulasi sertifikasi halal, meliputi konsep halal haram, landasan Al-Qur'an dan fatwa MUI, titik kritis keharaman, identifikasi bahan najis, serta peran LPPOM MUI. Pendekatan deskriptif kualitatif digunakan melalui wawancara mendalam, observasi, dan dokumentasi, dengan informan dipilih secara snowball sampling serta validitas data melalui triangulasi sumber. Temuan menunjukkan peningkatan signifikan pada jumlah pendamping sertifikasi halal di IAIN Kediri sebesar 82%, sementara jumlah sertifikat halal yang berhasil diterbitkan mencapai 99%. Meskipun demikian, seluruh informan hanya memiliki pemahaman parsial dan simbolis, lebih berorientasi pada label halal daripada sistem jaminan halal yang berkelanjutan. Sebagian besar tidak memahami titik kritis, kewajiban pasca-sertifikasi, maupun fungsi LPPOM MUI. Penelitian ini menyimpulkan bahwa pencapaian sertifikat administratif tidak menjamin kepatuhan regulasi. Oleh karena itu, pendampingan berkelanjutan dan pengawasan pasca-sertifikasi sangat direkomendasikan.